Recent advances in the microencapsulation of omega-3 oil and probiotic bacteria through complex coacervation: A review. (January 2018) - Eratte, Divya; Dowling, Kim; Barrow, Colin J.; Adhikari, Benu
Abstract: Background: Functional foods are a fastest growing sector of the food industry. The development of functional foods comprising omega-3 fatty acids and probiotic bacteria, through complex coacervation process is an emerging area of research and product development. Scope and approach: We reviewed relevant literature concerning the use of complex coacervation in microencapsulation, focusing primarily on the inclusion of probiotic bacteria and omega-3 oils into a single delivery format. This review covers advantages and disadvantages of the complex coacervation process to microencapsulate bioactive ingredients, viability of probiotic bacteria and oxidative stability of omega-3 oil during the complex coacervation process, the bioaccessibility of omega-3 oil and probiotic bacteria during simulated gastrointestinal conditions and in-vivo testings. Key findings and conclusions: The review describes the advantages of co-encapsulation using complex coacervation followed by spray drying. It also describes the technological hurdles that need to be resolved for further development of industrial applications of co-encapsulation of probiotic bacteria and omega-3 lipids. The co-encapsulation concept has been widely used in pharmaceutical delivery systems, but is a relatively new concept in food ingredient stabilisation and delivery. There is a commercial need of co-encapsulation of multiple bioactive ingredients within a single microcapsules, due to decreased cost and enhanced product quality. Complex coacervation has been shown to be a useful method for the co-encapsulation of multiple unstable bioactive ingredients. Although in-vitro evaluation deliver useful bioavailability information, additional in-vivo and clinical trials are needed to determine the efficacy of bioactive release, particularly for microcapsules containing multiple bioactive ingredients. Highlights: Various aspects of protein-polysaccharide complex coacervation is discussed. Microencapsulation of omega-3 oil and probiotic bacteria through complex coacervation is reviewed. Bioaccessibility of omega-3 oil and probiotic bacteria is investigated. The progress in co-encapsulation of omega- 3 oil and probiotic bacteria is summarized. Key areas of co-encapsulation in which further research is needed are highlighted.